Pengaruh Prestasi Belajar, Motivasi Kerja Dan Self-Efficacy Terhadap Kesiapan Kerja: Studi pada Mahasiswa Akhir Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta - Husna Ghoida; M.Farid Wajdi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to explore the impact of Academic Achievement, Work Motivation, and Self-Efficacy on the Job Readiness of final-year students at the Faculty of Economics and Business, Universitas Muhammadiyah Surakarta. The research subjects include all final-year students in the faculty, with a total of 120 respondents obtained through an online survey using Google Forms. The sampling technique adopts a non-probability sampling approach with the purposive sampling method. In data analysis, tests for validity, internal consistency (reliability), and detection of inter-variable relationships (multicollinearity) were conducted using Smart PLS analysis in the Outer Model. Meanwhile, hypothesis testing was carried out through the Inner Model using the same tool. The findings of this study indicate that Academic Achievement, Work Motivation, and Self-Efficacy have a positive and significant impact on students' Job Readiness.